Evaluation of multi-institutional end-to-end testing for post-operative spine stereotactic body radiation therapy. (October 2020) - Furuya, Tomohisa; Lee, Young K.; Archibald-Heeren, Ben R.; Byrne, Mikel; Bosco, Bruno; Phua, Jun H.; Shimizu, Hidetoshi; Hashimoto, Shimpei; Tanaka, Hiroshi; Sahgal, Arjun; Karasawa, Katsuyuki
Highlights: Post-operative spine SBRT may be a therapeutic option for patients with metal fixation. Evaluation of accuracy of dose prescription is a significant challenge. A phantom was created and circulated to 5 international centers. The impact of metal on dose delivered to both target and spinal cord was negligible. Abstract: Background and purpose: Post-operative spine stereotactic body radiation therapy (SBRT) represents a significant challenge as there are many restrictions on beam geometry to avoid metal hardware as it surrounds the target volume. In this study, an international multi-institutional end-to-end test using an in-house spine phantom was developed and executed. The aim was to evaluate the impact of titanium spine hardware on planned and delivered dose for post-operative spine SBRT. Materials and methods: Five centers performed simulation, planning and irradiation of the spine phantom, with/without titanium metal hardware (MB/B), following our pre-specified protocol. The doses were calculated using the centers' treatment planning system (TPS) and measured with radiophotoluminescent glass dosimeters (RPLDs) embedded within each phantom. Results: The dose differences between the RPLD measured and calculated doses in the target region were within ± 5% for both phantoms studied. Differences greater than 5% were observed for the spinal cord and the out-of-the target regions due to steeper dose gradient regions that are created in these plans. Dose measurements within ± 3% were observed between RPLDs that were embedded in MB and B inserts. For the spinal cord and the out-of-target regions surrounded by metal hardware, the dose measured using RPLDs was within 3% different near the titanium screws compared to the dose measured near only the metal rods. Conclusion: We have successfully performed the first multi-institutional end-to-end dose analysis using an in-house phantom built specifically for post-operative spine SBRT. The differences observed between the measured and planned doses in the presence of metal hardware were clinically insignificant.